A Rare Case of Meconium Periorchitis Diagnosed in Utero - Daigo Ochiai; Sayu Omori; Toshiyuki Ikeda; Kazumi Yakubo; Tatsuro Fukuiya (Case Reports in Obstetrics and Gynecology)
Meconium periorchitis is a rare disorder caused by fetal meconium peritonitis, with subsequent passage of meconium into the scrotum via a patent processus vaginalis. To date, clinical significance of meconium periorchitis for the prenatal diagnosis of meconium peritonitis and prediction for postnatal surgery remains to be determined. We present a clinical course of a fetus presenting with meconium periorchitis induced by meconium peritonitis. At 28 weeks’ gestation, fetal ultrasonography indicated fetal ascites associated with bilateral hydrocele and peritesticular calcification without other signs of meconium peritonitis. The pregnancy was uneventful until delivery and the infant was delivered at 37 weeks’ gestation. No abdominal distension was observed at birth, and radiography did not reveal any abdominal calcification except for scrotal calcification. Abdominal distension was observed 3 days after birth and laparotomy was performed. The diagnosis of meconium peritonitis was confirmed at surgery. Our case illustrated that careful examination of the scrotum during fetal life was helpful for prenatal diagnosis of meconium peritonitis as well as postnatal management.